The Effect of Giving of Telang Flower Extract (Clitoria ternatea) on Degenerative Hepatocytes and Liver Necrosis of Mice Exposed to Cigarette Smoke - Suprijono Agus; Wulansari Ariani Hesti; Setyoningsih Endang (E3S Web of Conferences)
Exposure to cigarette smoke is one of the risk factors for the onset of various diseases, Cigarette smoke contains high levels of free radicals so that it can cause cell damage, one of which is hepatocyte cells to cause necrosis. Telang flower extract has properties as an antioxidant. Flavonoids that function as antioxidants can reduce the number of free radicals formed from the lipid peroxidation process. This research aims were to determine the effect of telang flower extract on degenerative hepatocytes and necrosis of liver cells in mice exposed to cigarette smoke. This was an experimental research method with a post-test only controlled group design. Sample of this research was 25 mice were divided into normal groups (N). negative control (C-) was given exposure to cigarette smoke 2.25 mg/100 gBW, sample 1 (S1) was given telang flower extract 400 mg/kgBW and exposure to cigarette smoke 0.75 mg/100 gBW, sample group 2 (S2) was given extract 400 mg/kgBW and exposure to cigarette smoke 1.50 mg/100 gBW and sample 3 (S3) was given extract 400 mg/kgBW and exposure to cigarette smoke 2.25 mg/100 gBW The treatment was carried out for 7 day and continued with observation and calculation of degenerative hepatocytes and necrosis. The results that the negative control showed an increase in degenerative hepatocytes and necrosis by 157.8% and 81.29%, while in samples 1.2 and 3 after being given telang extract, there was an average decrease in degenerative by 74.1%, 51.06% and 3.27% and a decrease in necrosis of 400mg/kgBW by an average of 24.91%, 17.08% and 14.23%, The gived of telang flowers extract can reduce degenerative hepatocytes and necrosis due to exposure to cigarette smoke.